Fidelity considerations in translational research: Eating As Treatment — a stepped wedge, randomised controlled trial of a dietitian delivered behaviour change counselling intervention for head and neck cancer patients undergoing radiotherapy. Issue 1 (December 2015) - Beck, Alison; Baker, Amanda; Britton, Ben; Wratten, Chris; Bauer, Judith; Wolfenden, Luke; Carter, Gregory
Abstract Background The confidence with which researchers can comment on intervention efficacy relies on evaluation and consideration of intervention fidelity. Accordingly, there have been calls to increase the transparency with which fidelity methodology is reported. Despite this, consideration and/or reporting of fidelity methods remains poor. We seek to address this gap by describing the methodology for promoting and facilitating the evaluation of intervention fidelity in The EAT (Eating As Treatment) project: a multi-site stepped wedge randomised controlled trial of a dietitian delivered behaviour change counselling intervention to improve nutrition (primary outcome) in head and neck cancer patients undergoing radiotherapy. Methods/Design In accordance with recommendations from the National Institutes of Health Behaviour Change Consortium Treatment Fidelity Workgroup, we sought to maximise fidelity in this stepped wedge randomised controlled trial via strategies implemented from study design through to provider training, intervention delivery and receipt. As the EAT intervention is designed to be incorporated into standard dietetic consultations, we also address unique challenges for translational research. Discussion We offer a strong model for improving the quality of translational findings via real world application of National Institutes of Health Behaviour Change Consortium recommendations. Greater transparency in the reporting of behaviour change research is an important step in improving the progress and quality of behaviour change research. Trial registration number ACTRN12613000320752 (Date of registration 21 March 2013)